The Application of Architectural Concepts in Church Design: A Case Study of the Seventh-day Adventist Church: Penelitian - Edgar W. M. Tauran (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The design of a church building involves more than functional and structural aspects; it also encompasses symbolic, spiritual, and cultural values. This study analyzes the application of architectural concepts in the design of the Church through a literature review and field study approach. The results show that the church’s design not only reflects religious values but also accommodates strong historical and aesthetic elements through architectural components such as building orientation, fundamental forms, natural lighting, and religious symbols. The overall design integrates sacred and social functions harmoniously, making the church a spiritual center as well as a community space.